O cristianismo e a crítica à modernidade na obra O Anticristo de Nietzsche - Silva, Diego Wendell da (2015)
The present study starts from Nietzsche's psycho-physiologist analysis of Christianity and investigates its relation with the body, defined here as a dynamic space of agonistic processes among forces. Thus, we highlight Nietzsche's criticism to consciousness, to the status of the ´Self´ as a product of bodily processes, that allows us to understand what he called as the process of décadence. In the first part, we assess the way in which the Christian ideal deny and depreciate life while aiming for a world beyond, the true world; such elements are symptons of degeneration and of a frail vitality, characterizing features of décadence. Thereafter, we investigate the genealogy of Christianity in Nietzsche's work, The Antichrist. We try to rebuild all the structure that allowed the emergence of the Christian mindset within the Hebrew culture. We shall see that all eevaluative processes towards existence might be understood as physiological processes that expresses the dynamic of forces that compose the body of individuals, as well as the cultural bodies. These eevaluative processes are also expression of possible configurations among the multiple forces that make reality. At last, we investigate Modernity and its roots on Christianity by elucidating how the modern mentality kept its metaphysical core, even while trying to overcome the Christian ideal. According to Nietzsche, western civilization is the natural unfoldment of the Christian ideal as a set of civilizatory ideas, the slow domestication of the instincts. Even ideas that seems to contend the legitimacy of christian religion, like the ideas of democracy, science and progress, are derived from the Christian mindset, they are just symptoms of the process of décadence.